Technology as a pathway for older people to engage in activities promoting successful ageing - Teixeira-Santos, L.; Bobrowicz-Campos, E.; Ventura, F.; Parola, V.; Coelho, A.; Almeida, M. L.; Gil, I.; Moreno-Casbas, M. T.; Apóstolo, J. (Exploring the role of ICTs in healthy aging, 2020)
This chapter focuses on the use of technology on older adult health promotion. During the ageing process, they experience changes in physical, cognitive, psychological, and social domains. Frailty is the most problematic expression of ageing and entails a high risk of adverse outcomes. In order to prevent it, healthcare professionals must intervene on health promotion. However, it's impossible to continuously monitor the health status of thousands of people. Technologies can bridge the gap between older people's home and the hospital. Especially those with sensors, allow healthcare professionals to continuously monitor the older people's health status and evaluate the health parameters to prioritize care and alert to necessary behavioral changes. The seniors become more aware and responsible for their health, increasing their literacy, autonomy, and well-being. They become more engaged in activities that promote successful ageing. In this chapter, the authors address one of many research projects that monitor the health parameters of older people in a community setting through wearable sensors.